2018
DOI: 10.1039/c8ra04514c
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effect of HOTAIR–miR-613-SNAI2 axis through suppressing EMT and drug resistance in laryngeal squamous cell carcinoma

Abstract: Laryngeal squamous cell carcinoma (LSCC) is the main pathological type of laryngeal cancer, which attacks the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Baygi et al., observed Snai2 was significant up-regulated in prostate carcinoma cell lines and could promote the EMT [33]. It was also showed the miR-613 could down-regulate Snai2 expression and further suppress EMT in LSCC [34]. In the present study, we also found Snai2 was increased in LSCC.…”
Section: Discussionsupporting
confidence: 78%
“…Baygi et al., observed Snai2 was significant up-regulated in prostate carcinoma cell lines and could promote the EMT [33]. It was also showed the miR-613 could down-regulate Snai2 expression and further suppress EMT in LSCC [34]. In the present study, we also found Snai2 was increased in LSCC.…”
Section: Discussionsupporting
confidence: 78%
“…A variety of kidney cancer-related genes and signaling pathways have been discovered, and many targeted therapeutic drugs have been introduced. However, their therapeutic effects on renal cancer are still limited, and there are still resistance problems [7][8][9]. Therefore, the majority of medical workers need to carry out further basic experiments to study the pathogenesis of renal cell carcinoma, and the changes of signal transduction pathways in cancer cells and the changes of oncogene or tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that dysregulated expression of HOTAIR is strongly linked to proliferation, metastasis, and invasion of HNSCC, and abnormally expressed LncRNA may be a significant inducer and accelerator of tumor development and metastasis. 37 When compared with healthy oral mucosa tissues and oral keratin-forming cells, OSCC tissues and Hep-2/R and TU686/R cell lines showed increased expression of HOTAIR. The level of this expression was also positively correlated with the tumor lymph node metastasis (TNM) stage, histological grade, and regional lymph node metastasis.…”
Section: Abnormal Expression Of Hotair In Hnsccmentioning
confidence: 95%